EVALUASI RUANG PARKIR MITRA 10 KENDARI - La One; Ridwan Syah Nuhun; La Ode Muh. Akbar Yasin; La Welendo; Tapsil; Zaitun Andarwan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Parking facilities are an important element in supporting visitor activities in the trade center. Mitra 10 Kendari as a relatively new building materials store needs to be evaluated to find out the characteristics of parking and the adequacy of parking space in existing conditions and future projections. This study aims to evaluate the characteristics of parking and parking space needs in Mitra 10 Kendari for the next 10 years and 20 years. The research was conducted through a three-day direct parking survey, namely Friday, Saturday, and Sunday. The data analyzed includes parking accumulation, parking duration, parking turnover rate, parking capacity, and parking index, as well as forecasting parking needs based on existing conditions. The results of the analysis show that in the existing conditions, the parking capacity of Mitra 10 Kendari is still adequate with the availability of 87 SRPs for four-wheeled vehicles and 25 SRPs for two-wheeled vehicles as well as the parking index value below one (IP < 1). However, the projection results show that in the next 10 years the need for parking is estimated to reach 40 four-wheelers and 44 two-wheelers, and in the next 20 years it will increase to 76 four-wheelers and 83 two-wheelers. The parking needs of two-wheeled vehicles are estimated to be unable to be accommodated by existing parking facilities, so additional parking spaces are needed in the future.